Periclimenaeus echinimanus sp. nov. (Crustacea: Decapoda: Pontoniinae), a new species from the Gulf of Aqaba, Red Sea - Ďuriš, Zdeněk; Horká, Ivona; Al–Horani, Fuad (Zootaxa, 2011)
A new species of sponge-associated pontoniine shrimp from the northeastern Red Sea is described and illustrated. The new species is closely related to Periclimenaeus rhodope, but can be easily distinguished from the latter by the dense spinulation of the second pereiopod chelae. The new species is placed in the Periclimenaeus robustus species group, on account of the presence of the anterodorsal median lobe on the first abdominal segment. The new species is the first representative of the genus reported from a discrete Red Sea locality.